THE APPLICABILITY OF CO-COMBUSTION OF COAL WITH SEWAGE SLUDGE: A REVIEW - Camera, S.; Pineda-Vásquez, T.; Bianchi, F. M.; Virmond, E.; Martins, L. S.; Watzko, E. S. (Revista de Engenharia Térmica, 2020)
Co-combustion of coal with a secondary fuel, as for example, waste-biomass, including sewage sludge, isan option for its safe its elimination and a sustainable alternative for heat and power generation. Untreated sewage sludge has a negative impact on the environment and society due to its compositional and pathogenic factors. Co-combustion of coal and sewage sludge have advantages over some emissions parameters and improvement of thermal characteristics, but there are limiting factors for its large-scale use, especially regarding to the fuel feed which requiresinnovative methods to develop a product that combinesboth fuels. When it comes to environmental impact, the combined combustion of and coal with sewage sludge presents good opportunities for future research and technological applications to be explored. This review focuses on the combination of coal and sewage sludge, highlighting the possibilities and limitations of the co-combustion using them as fuel.